2019
DOI: 10.1038/s41380-019-0458-5
|View full text |Cite
|
Sign up to set email alerts
|

Brain expression of the vascular endothelial growth factor gene family in cognitive aging and alzheimer’s disease

Abstract: Vascular endothelial growth factor (VEGF) is associated with the clinical manifestation of Alzheimer's disease (AD). However, the role of the VEGF gene family in neuroprotection is complex due to the number of biological pathways they regulate. This study explored associations between brain expression of VEGF genes with cognitive performance and AD pathology. Genetic, cognitive, and neuropathology data were acquired from the Religious Orders Study and Rush Memory and Aging Project. Expression of ten VEGF ligan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
69
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(77 citation statements)
references
References 48 publications
(73 reference statements)
7
69
1
Order By: Relevance
“…In comparison to the subtle effects between sham and blast at each time-point, when we compared the transcriptome of sham animals at the chronic vs. sub-acute time-points, we found an abundance of genes differentially expressed and surviving correction for multiple testing. These changes emphasize the large effect of aging on gene expression in the amygdala, and we identified significant alterations in expression levels of various genes that have previously been associated with normal aging and neurodegeneration, including Gfap (Rodríguez et al, 2014), Vegfb (Mahoney et al, 2019), FIGURE 6 | Gene ontology enrichment using Ingenuity Pathway Analysis (IPA). (A) Top 10 gene categories.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…In comparison to the subtle effects between sham and blast at each time-point, when we compared the transcriptome of sham animals at the chronic vs. sub-acute time-points, we found an abundance of genes differentially expressed and surviving correction for multiple testing. These changes emphasize the large effect of aging on gene expression in the amygdala, and we identified significant alterations in expression levels of various genes that have previously been associated with normal aging and neurodegeneration, including Gfap (Rodríguez et al, 2014), Vegfb (Mahoney et al, 2019), FIGURE 6 | Gene ontology enrichment using Ingenuity Pathway Analysis (IPA). (A) Top 10 gene categories.…”
Section: Discussionmentioning
confidence: 73%
“…Significant interactions included Plpp3, which is enriched in the ventral midbrain and has been linked to dopaminergic functioning in the striatum but not yet linked to the amygdala function (Gómez-López et al, 2016). Of the abundant interactions that did not survive multiple testing correction, we chose to highlight four additional genes that have known roles in brain injury and/or amygdala functioning, including Apoe (Klein et al, 2014;Tang et al, 2015), Reln (Boyle et al, 2011;Frankowski et al, 2019), Vegfb (Wu et al, 2008;Savalli et al, 2014;Mahoney et al, 2019), and Bdnf (Wu et al, 2008;Guilloux et al, 2012;Sagarkar et al, 2017), which are all crucial mediators of synaptic plasticity and neurotransmission as well as structure and function of brain vasculature. Interestingly, Plpp3, Apoe, Reln, and Vegfb show similar patterns of interaction, such that expression levels in blast animals are higher than sham animals at the sub-acute timepoint but lower than sham animals at the chronic time point.…”
Section: Discussionmentioning
confidence: 99%
“…Genes involved in regulation of VEGF signaling were enriched among GxS loci for MDD in our analyses. Sex differences have been observed in serum VEGF levels throughout life (91), and brain expression of VEGF has been associated with cognitive aging and Alzheimer's disease (92,93). Further, the strongest GxS interaction was detected for SCZ in the 5' UTR of MOCOS (rs11665282; p=1.48×10 −7 ), which, based on evaluation of brain expression datasets, is highly expressed in endothelial cells lining blood vessels (Supplementary Figure 24).…”
Section: Several Mechanisms Could Account For Opposite Direction Intementioning
confidence: 98%
“…Metabolic syndrome (a primary risk factor of VCID) is frequently associated with elevated blood levels of ADMA 7,8 and VEGF 46,47 and increased microvascular pathology in the brain 48 . More recently, studies also reported that patients with cognitive aging and AD had a greater expression of endothelial growth factor gene family, including VEGF, in the brain and serum and the degree of VEGF expression well correlated with the severity of dementia 49,50 . It is of interest note that Tg‐SwDI mice had increased blood levels of VEGF (Figure 7B‐iii) and daily ADMA treatment increased the brain N‐Tyr levels further in Tg‐SwDI mice (Figure 7A).…”
Section: Discussionmentioning
confidence: 90%